IMPLEMENTATION OF THE GOVERNMENT AGENCY PERFORMANCE ACCOUNTABILITY SYSTEM (SAKIP) AT THE COMMUNICATION, INFORMATICS, CRYPTOGRAPHY AND STATISTICS SERVICE OF PALU CITY - Rahmawati; Mahfuzat; Darwis (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to determine the implementation of the government agency performance accountability system (SAKIP) policy at the Palu City Communication, Informatics, Cryptography, and Statistics Office. This study used qualitative methods with data collection techniques including observation, interviews, and documentation. Five subjects were selected through purposive sampling. The results indicate that, in terms of policy content, the implementation of SAKIP has had a positive impact on increasing effectiveness, efficiency, and performance accountability, as well as encouraging a transformation of work culture toward a results-oriented one. However, constraints remain in the form of limited human resources, both in terms of quantity and capacity for outcome-based performance, as well as limited budget for training and competency development. In terms of implementation context, SAKIP implementation is supported by a clear organizational structure, collaborative coordination between internal and external actors, and a high level of regulatory compliance. Although the work culture tends to be formal and bureaucratic, the agency is unable to implement cross-sectoral coordination and be responsive to external input. Public perception is influenced by four factors: motives, interests, experience, and expectations. In conclusion, SAKIP implementation at the Palu City Communications and Informatics Office has progressed in a positive direction, but requires continued strengthening of human resource capacity, inter-agency coordination, and optimization of information technology utilization to ensure a more effective, efficient, and sustainable performance accountability system.